2006
DOI: 10.1530/eje.1.02153
|View full text |Cite
|
Sign up to set email alerts
|

Association of dehydroepiandrosterone-sulfate with endothelial function in young women with polycystic ovary syndrome

Abstract: Objective: The aim of this study was to assess non-invasively endothelial function of young women with polycystic ovary syndrome (PCOS) in comparison with healthy age-matched women and a group of young women with idiopathic hirsutism (IH). The possible role of metabolic and hormonal parameters on endothelial function was also examined. Design: Descriptive clinical trial. Methods: Fifty-six women, 27 with PCOS, 16 with IH and 13 healthy age-matched women were studied. Endothelial function of resistance arteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 59 publications
5
19
0
1
Order By: Relevance
“…Consistent with our results, most of the studies, but not all [8,12], demonstrated impaired endothelial function in PCOS using either noninvasive endothelium-dependent (FMD) and-independent (glyceroltrinitrate, GTN) changes in the brachial artery or invasive methodology [4,6,10,11,24] compared with the controls. Among several circulating endothelium-derived vasoactive molecules, ET-1 is considered one of the best indices of abnormal vascular reactivity, playing an important role in the early events of endothelial dysfunction [4].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with our results, most of the studies, but not all [8,12], demonstrated impaired endothelial function in PCOS using either noninvasive endothelium-dependent (FMD) and-independent (glyceroltrinitrate, GTN) changes in the brachial artery or invasive methodology [4,6,10,11,24] compared with the controls. Among several circulating endothelium-derived vasoactive molecules, ET-1 is considered one of the best indices of abnormal vascular reactivity, playing an important role in the early events of endothelial dysfunction [4].…”
Section: Discussionsupporting
confidence: 89%
“…Conflicting results have been provided regarding the factors associated with impaired vascular reactivity in PCOS. The relationship with hyperandrogenemia is especially controversial, since the effect of the androgens was described as either adverse [10,25], neutral [24,26], or even protective in patients with PCOS [27]. However, the reports are more constant with regard to ET-1 and the deleterious effect that markers of hyperandrogenemia have on it [3,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma DHEA-S levels do not drop during the menopause transition, but decline with aging (1,2,20). A recent study has shown a positive correlation between DHEA-S levels and the duration of reactive hyperemia, another less specific marker of endothelial function compared to FMD, in young women (26±6 years old, n= 27) with polycystic ovary syndrome (21). In postmenopausal women, however, a correlation between DHEA-S levels and endothelial vasomotor function has not yet been reported.…”
Section: Discussionmentioning
confidence: 92%
“…Height and weight were measured and endothelial function was tested, as described below. Endothelial function of the resistance vessels was assessed by measuring forearm blood flow (FBF) before and after upper arm arterial occlusion (21)(22)(23)(24). The stable isotope labeled frequently-sampled intravenous glucose tolerance test and minimal modeling were used to assess insulin secretion and secretion (25).…”
Section: Protocolmentioning
confidence: 99%